Pengembangan Nilai Pendidikan Karakter Islami di Masa Pandemi COVID-19 (Studi Analisis di Universitas Islam Sumatera Utara) - Nurhaizan Sembiring; Parlaungan Lubis; Ghaffariel I Aura (UIN Fatmawati Sukarno Bengkulu, 2023)
The corona pandemic that has hit several countries, including Indonesia, has had a significant impact on the world of education, the corona virus is an infectious disease that can be prevented in several ways. One of them is by avoiding and limiting crowds. Based on this, the government instructed to carry out activities by working and studying from home. Of course, there has been a change in the learning method, from face-to-face to virtual face-to-face learning by relying on the network and internet data quota with a sophisticated technology application system, namely the Google Meet, Zoom and WhatsApp applications. Virtual face-to-face learning with these various applications is expected to be able to carry out learning while developing the value of character education in the face-to-face period. Based on the results of the questionnaire that has been answered, optimistically the Islamic character values are still being carried out in a fully effective manner, that is, ethical/manner values are still being implemented and maintained by lecturers and students, carrying out lecture duties and responsibilities by carrying out and presenting assignments properly and intelligence in using technology which is also a new culture in learning during the current pandemic.